Interleukin 22 serum levels are associated with radiographic progression in rheumatoid arthritis. Issue 8 (18th May 2011) - Leipe, Jan; Schramm, Markus A; Grunke, Mathias; Baeuerle, Michael; Dechant, Claudia; Nigg, Axel P; Witt, Matthias N; Vielhauer, Volker; Reindl, Christiane S; Schulze-Koops, Hendrik; Skapenko, Alla
Abstract : Objectives: To study the role of interleukin 22 (IL-22) in rheumatoid arthritis (RA). Methods: IL-22 serum levels were measured in patients with early, treatment-naive RA (n=49) and in 45 age- and sex-matched healthy individuals as controls. Patients were assessed clinically and radiographically at baseline and followed up for 2 years. Correlations of IL-22 serum levels were sought with parameters of disease activity, serological markers, demographic factors and the incidence of erosions. IL-22 production by peripheral blood T cells was investigated by intracellular flow cytometry. Results: 24 of 49 patients with RA demonstrated elevated IL-22 levels compared with the range of healthy controls. At baseline, a high percentage of these patients (8/24, 33%) demonstrated bone erosions, whereas only one patient (4%) from the group with normal IL-22 had erosions. During the 2 years of follow-up, six additional patients with increased IL-22 at baseline developed erosions. In contrast, none of the patients in whom IL-22 levels were normal developed erosions despite similar treatment regimens. Multivariate regression analysis accounting for other parameters predictive for erosions, such as the presence of rheumatoid factor or anti-cyclic citrullinated peptide antibodies and disease activity, showed that elevated IL-22 baseline levels were independently and significantly associated with erosive RA. Cellular analysis demonstrated enhanced expression of IL-22 from CD4 T cells in RA. Conclusion: IL-22 is elevated in the serum of half of the patients with RA. Elevated serum IL-22 allows discrimination between patients with different radiographic progression and indicates a possible involvement of IL-22 in the pathophysiology of RA.